Bargaining in the absence of property rights: An experiment - Oren Bar-Gill; Christoph Engel (Max Planck Institute for Research on Collective Goods, 2015)
The Coase theorem posits: If [1] property rights are perfect, [2] contracts are enforceable, [3] preferences are common knowledge, and [4] transaction costs are zero, then the initial alloca-tion of property rights only matters for distribution, not for efficiency. In this paper we claim that condition [1] can be dropped and show experimentally that this is also empirically true. This also holds when we frame taking as "stealing" and when the initial possessor has to work for the good.
Keywords: C91; D01; D02; D03; D47; D61; K11; 330; coase theorem; absolute vs. relative right; bargaining; efficiency; distribution; fairness